Analyzing Learner’s Computational Thinking in Designing Home ISP Service Structure (International Journal of Active Learning, 2023)
This study aims to analyze the ability of computational thinking in solving network structure design case study problems. This study presented a  case study method given to participants of the research  . They were also given fifteen interview questions to the research subjects at SMK Negeri 2 Salatiga. The interview questions posed contain meaning and computational thinking skills that have been adopted and adapted to the existing problems. The results of this study indicate that students can identify and extract relevant information, divide complex problems into small parts and determine priorities which are the key to problem solving, identify and find similarities in problem solving patterns, compare and map problem solving concepts, design a sequence of problem solving steps in a structured and logical manner, be able to evaluate and assess the solutions they design to solve the problems in the case study.